Teacher Strategies in Improving Literacy Comprehension Skills in Grade IV Students in Primary Schools - Ahmad Hariandi; Asril Asril; Zubaedah Zubaedah (Indonesian Language and Literature Education Study Program and LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2020)
This study aims to describe the strategies implemented by teachers in improving literacy comprehension in grade IV F students of SD Negeri 47 / IV Jambi City. This research is a qualitative research. The subjects in this study were the fourth grade F. homeroom teacher. The data in this study were obtained through observations during the learning process, the interview with the homeroom teacher IV F, as well as documentation of learning activities, lesson plans, and reading texts in student books. After the data is collected, the data is checked using triangulation techniques and analyzed using the Miles and Huberman models with the stages of reducing data, presenting data, and drawing conclusions / verification. The results of this study indicate that the strategies implemented by teachers in improving literacy comprehension in grade IV F students of SD Negeri 47 / IV Jambi City, are ReQAR strategies, with the steps used by teachers in learning as follows: 1) teachers begin by conditioning students first before learning begins; 2) the teacher asks students to silently read the reading text; 3) the teacher asks questions to students; 4) the teacher asks students to ask questions; 5) teachers and students do question and answer about the reading text. Abstrak Penelitian ini bertujuan untuk mendeskripsikan strategi yang diimplementasikan guru dalam meningkatkan kemampuan membaca pemahaman literal pada peserta didik kelas IV F SD Negeri 47/IV Kota Jambi. Penelitian ini merupakan penelitian kualitatif. Subjek dalam penelitian ini adalah guru wali kelas IV F. Data dalam penelitian ini diperoleh melalui hasil observasi selama proses pembelajaran berlangsung, wawancara terhadap guru wali kelas IV F, serta dokumentasi kegiatan pembelajaran, RPP, dan teks bacaan pada buku siswa. Setelah data terkumpul, data dicek menggunakan triangulasi teknik dan dianalisis menggunakan model Miles dan Huberman dengan tahapan mereduksi data, menyajikan data, dan mengambil kesimpulan/verifikasi. Hasil penelitian ini menunjukkan bahwa strategi yang diimplementasikan guru dalam meningkatkan kemampuan membaca pemahaman literal pada peserta didik kelas IV F SD Negeri 47/IV Kota Jambi, adalah strategi ReQAR, dengan dengan langkah yang digunakan guru dalam pembelajaran sebagai berikut: 1) guru mengawali dengan mengkondisikan peserta didik terlebih dahulu sebelum pembelajaran dimulai; 2) guru meminta peserta didik untuk membaca dalam hati teks bacaan tersebut; 3) guru mengajukan pertanyaan kepada peserta didik; 4) guru meminta peserta didik bertanya; 5) guru dan peserta didik melakukan tanya jawab mengenai teks bacaan. Kata kunci: strategi guru, membaca pemahaman literal